AB0885 Anti-Cyclic Citrullinated Peptide (ANTI-CCP) Antibodies in Polyarticular Juvenile Idiopathic Arthritis at Adulthood. (10th June 2014) - Frantz, C.; Bazeli, R.; Elhai, M.; Feydy, A.; Deslandre, C.; Wipff, J.
Abstract : Background: Several studies have already focused on anti-cyclic citrullinated peptide (anti-CCP) antibodies in juvenile idiopathic arthritis (JIA). Results of these studies showed that anti-CCP were associated with polyarticular sub-type (pJIA) and more severe disease, especially for structural damages. However, these studies analysed global JIA without focusing on the polyarticular form and especially on rheumatoid factors (RF) positive pJIA. Objectives: Determine the prevalence of anti-CCP and evaluate their clinical and radiographic significance in polyarticular JIA at adulthood. Methods: Anti-CCP antibodies were determined in a large cohort of polyarticular form of JIA at adulthood. Following demographic and clinical data were collected: sex, age at diagnostic, medical treatments (corticosteroids, DMARDs and biotherapies), history of surgery, number of synovitis and C-reactive protein at the last medical visit. Rheumatoid factors (RF) and antinuclear antibodies (AAN) have been collected. Radiographic damages were evaluated by the Sharp Van Der Heijde score. Results: 56 patients with polyarticular form of JIA, fulfilling the ILAR criteria, persisting at adulthood were included with mean age of 25±8.1 years and mean disease duration of 14.3±8.7 years. Antibodies status (anti-CCP, RF and AAN) was performed after a mean of 11.6±9 years after the diagnosis. 29/56 (52%) patients were anti-CCP positive. Anti-CCP positive pJIA had a significant association with presence of RF (97% vs 26%, p<0.0001), a higher use of biotherapies (86% vs 70%, p=0.02, OR=4.3 [1.2-15.8]) and were older at diagnosis (13±3.4 vs 7.6±4.9, p=0.00001) than anti-CCP negative patients. No differences have detected for sex, presence of antinuclear antibodies, synovitis, CRP, Corticosteroids, DMARDs and surgery. Radiographic damages were similar between the two sub-groups for erosion (16.2±21.3 vs 14.8±28.3), joint space narrowing (24.3±29.3 vs 23.8±34.9) and total scores (40.4±46.8 vs 38.7±61.8). In the sub-group of RF positive pJIA (n=35), 28 were anti-CCP positive and 7 negative. No differences for sex, clinical data, medical treatments, surgery and radiographic damages have been detected. Conclusions: In this large cohort of polyarticular JIA patients at adulthood, anti-CCP antibodies are associated with a higher need of biotherapies but not with a more structural radiographic severe disease. A small sub-group of patients were RF+ and anti-CCP-. Comparison of RF+ and anti-CCP+ and RF+ and anti-CCP- patients showed that anti-CCP did not seem to bring more information as RF but a larger cohort will be necessary to confirm these results. Finally, our results suggest that polyarticular JIA patients evolving at adulthood are independent of anti-CCP antibodies status at the difference of the pJIA in childhood in which anti-CCP status remains a poor prognostic factor. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5319